2022
DOI: 10.1177/15459683221110894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Robot-Assisted Training on Unilateral Spatial Neglect After Stroke: Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background Several studies have shown that robotic devices can effectively improve motor function in stroke patients through limb activation. However, the effects of robot-assisted therapy on perceptual deficits after stroke is unclear. Objective This review aimed to evaluate the effectiveness of robotic limb activation in patients with unilateral spatial neglect (USN) after stroke. Methods In this systematic review, a literature search was performed using MEDLINE, EMBASE, CENTRAL, CINAHL, and LILACS databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…78 A recent review reported improved midline perception as measured by line bisection but not in visual scanning and function-focused USN outcomes following robotassisted USN interventions. 79…”
Section: Robot-assisted Interventionmentioning
confidence: 99%
“…78 A recent review reported improved midline perception as measured by line bisection but not in visual scanning and function-focused USN outcomes following robotassisted USN interventions. 79…”
Section: Robot-assisted Interventionmentioning
confidence: 99%
“…Rehabilitation intervention for USN ranges from robotics to virtual reality to prism adaptation training. The robotic training may enhance midline orientation altered due to neglect; however, the training induces no significant effect on functional performance [ 22 ]. The virtual reality intervention has potential for the USN, yet good quality randomized trials are lacking [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…USN is considered to be a common cognitive deficit that substantially contributes to post-stroke disability [20]. USN not only increases the functional disability of the individuals who had a stroke but also adds to the burden on the family or caretaker [21].…”
Section: Introductionmentioning
confidence: 99%